ANALISIS PENGARUH BRAND AWARENESS DAN BRAND IMAGE TERHADAP MINAT PEMBELIAN DAN KAITANYA DENGAN INISIASI ONE VILLAGE ONE PRODUCT DI KABUPATEN KUNINGAN - Vigory Gloriman Manalu; Ilham Akbar (Universitas Muhammadiyah Metro Lampung, 2020)
OVOP (one village one product) started in Oita Prefecture in southwest of Japan in the late 1970s and aimed to revitalize the prefecture's rural economy. In Indonesia, the OVOP policy is also stated in the Presidential Instruction of the Republic of Indonesia number 6 year 2007, which is to encourage the development of promotion institutions and the creation of MSME products through the OVOP approach. So far, there has been no research that examines the effect of brand image and brand awareness of local products on the interest in purchasing local products with OVOP as antecedent. This method is part of the Non-Probability Sampling method in which the sample is drawn based on the criteria determined by the researcher, that is, anyone who happens to meet the researcher and meets the criteria can be used as a sample. Furthermore, Brand Image and Brand Awareness have positive and significant effect on Purchase Intention for typical products of Kuningan Regency.Keywords: Brand Image, Brand Awareness, Purchase Intention, OVOP